Anti‐androgen enzalutamide enhances prostate cancer neuroendocrine (NE) differentiation via altering the infiltrated mast cells → androgen receptor (AR) → miRNA32 signals - Qiang Dang; Lei Li; Hongjun Xie; Dalin He; Jiaqi Chen; Wenbing Song; Luke S. Chang; Hong-Chiang Chang; Shuyuan Yeh; Chawnshang Chang (Molecular Oncology)
The recently developed anti‐androgen enzalutamide also known as (MDV3100) has the advantage to prolong by 4.8 months the survival of castration resistant prostate cancer (CRPC) patients. However, the mechanisms behind the potential side effects involving the induction of the prostate cancer (PCa) neuroendocrine (NE) differentiation remain unclear. Here we found PCa cells could recruit more mast cells than normal prostate epithelial cells, and enzalutamide (or casodex) treatment could further increase such recruitment that resulted in promoting the PCa NE differentiation. Mechanism dissection found infiltrated mast cells could function through positive feedback to enhance PCa to recruit more mast cells via modulation of the androgen receptor (AR) → cytokines IL8 signals, and interruption by AR‐siRNA or neutralizing anti‐IL8 antibody could partially reverse the recruitment of mast cells. Importantly, targeting the PCa androgens/AR signals with AR‐siRNA or enzalutamide (or casodex) also increased PCa NE differentiation via modulation of the miRNA32 expression, and adding miRNA32 inhibitor reversed the AR‐siRNA‐ or enzalutamide‐enhanced NE differentiation. Together, these results not only identified a new signal via infiltrated mast cells → PCa AR → miRNA32 to increase PCa NE differentiation, it also pointed out the potential unwanted side effects of enzalutamide (or casodex) to increase PCa NE differentiation. Targeting these newly identified signals, including AR, IL8, or miRNA32, may help us to better suppress PCa NE differentiation that is induced during ADT with anti‐androgen enzalutamide (or casodex) treatment.